2019
DOI: 10.5713/ajas.19.0381
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in breeding and genetics for dairy goats

Abstract: Goats ( Capra hircus ) were domesticated during the late Neolithic, approximately 10,500 years ago, and humans exerted minor selection pressure until fairly recently. Probably the largest genetic change occurring over the millennia happened via natural selection and random genetic drift, the latter causing genes to be fixed in small and isolated populations. Recent human-influenced genetic changes have occurred through biometrics and genomics. For the most part, biometrics has concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Single-step genomic best linear unbiased prediction (ssGBLUP; Legarra et al, 2009;Aguilar et al, 2010;Christensen and Lund, 2010) is a promising approach, as it enables the simultaneous integration of phenotypic records, pedigree, and genomic information to generate more accurate predictions of genomic estimated breeding values (GEBV; Guarini et al, 2018;Piccoli et al, 2018;Piccoli et al, 2020). The performance of ssGBLUP has been evaluated in various species, including dairy cattle (Kang et al, 2018;Guarini et al, 2019;Oliveira et al, 2019d), poultry (Chu et al, 2019), pigs (Song et al, 2019), beef cattle (Mehrban et al, 2019;Aguilar et al, 2019), and small ruminants (Gipson, 2019;Teissier et al, 2019). However, studies investigating the feasibility of genomic prediction of GEBV in buffalo remain scarce, especially for longitudinal traits.…”
Section: Introductionmentioning
confidence: 99%
“…Single-step genomic best linear unbiased prediction (ssGBLUP; Legarra et al, 2009;Aguilar et al, 2010;Christensen and Lund, 2010) is a promising approach, as it enables the simultaneous integration of phenotypic records, pedigree, and genomic information to generate more accurate predictions of genomic estimated breeding values (GEBV; Guarini et al, 2018;Piccoli et al, 2018;Piccoli et al, 2020). The performance of ssGBLUP has been evaluated in various species, including dairy cattle (Kang et al, 2018;Guarini et al, 2019;Oliveira et al, 2019d), poultry (Chu et al, 2019), pigs (Song et al, 2019), beef cattle (Mehrban et al, 2019;Aguilar et al, 2019), and small ruminants (Gipson, 2019;Teissier et al, 2019). However, studies investigating the feasibility of genomic prediction of GEBV in buffalo remain scarce, especially for longitudinal traits.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the size of the goat’s sphenoid bone body (13 mm in width) is similar to that of the human’s sphenoid sinus (20 mm in width), and there is no cortex in between the nasal cavity and the pre-chiasmatic ON ( Figure 1D ). Additionally, Saanen goats are readily available, easy to raise and handle, genetically editable ( Kalds et al, 2019 ), and have a genome that is well studied ( Araújo et al, 2006 ; Martin et al, 2018 ; Gipson, 2019 ). Therefore, we decided to use Saanen goat as our research animal model.…”
Section: Resultsmentioning
confidence: 99%
“…By use of the DNA marker and microarray technologies, the reference populations can be rapidly established with a large scale ( Kraus et al, 2015 ). Compared with other farming animals, the modern technology for dairy goat breeding has lagged behind for a while, but currently, it has also been advanced into the era of microarray breeding ( Gipson, 2019 ). By comparing the high and low fecundity of the dairy goats and sequencing their whole genes, Lai et al have identified some candidate genes related to reproductive traits including non-synonymous exon SNPs in SETDB2 and CDH26 genes ( Lai et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%